Synthesis and characterization of highly-fluorinated colorless polyimides derived from 4,4 '-((perfluoro-[1,1 '-biphenyl]-4,4 '-diyl)bis(oxy))bis(2,6-dimethylaniline) and aromatic dianhydrides - Yeo, Hyeonuk; Goh, Munju; Ku, Bon-Cheol; You, Nam-Ho (ELSEVIER SCI LTD, 2015)
The authors report the synthesis and characterization of a polyimide (PI) series derived from 4,4'-((perfluoro-[1,1'-biphenyl]-4,4'-diyl)bis(oxy))bis(2,6-dimethylaniline) (8FBPODMA). The 8FBPODMA monomer containing a perfluorobiphenyl group with two 2,6-dimethylaniline units connected by an ether bond was synthesized and polycondensed with several aromatic dianhydrides, including 4,4'-biphthalic anhydride (BPDA), 4,4'-oxydiphthalic anhydride (ODPA), pyromellitic dianhydride (PMDA), and 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), by the traditional two-step imidization procedure. All Pis shows high optical transparency, higher than 80% at 500 nm for a thickness of ca. 10 urn and good thermal properties. The thermal decomposition temperatures (T-10%) of the PIs are in the range of 507-527 degrees C and the glass transition temperatures (T-g) are in the range of 280-345 degrees C. In addition, the PIs have low refractive indices because of their high fluorine contents. In particular, 8FBPODMA-6FDA shows a very low refractive index (1.5389) and a low birefringence (0.0054) at 637 nm. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: SOLUBLE POLYIMIDES; OPTICAL-PROPERTIES; TRANSPARENT; 2,2-BIS(TRIFLUOROMETHYL)-4,4-DIAMINOBIPHENYL